Selected Aspects and Determinants of the Slovak Agro-Food Companies' Innovativeness - Moravčíková, Danka; Tkáč, Filip; Mušinská, Kristína (Frontiers in Sustainable Food Systems, 2021)
Sustainability and innovation are key elements of the economic growth and productivity in the contemporary era. The willingness, ability, and capacity to innovate is a strategic tool for the Slovak agro-food companies that want to maintain and/or to improve their market. The aim of this paper is to discuss the selected aspects and determinants of innovative performance of the Slovak agro-food companies and point out key areas and types in innovations, problems influencing their implementation, and assessing their success. The issue of innovation and the “new” role of the agro-food sector have become crucial in the context of transition of the Slovak economy toward more sustainable approaches. Therefore they have become important topics of both scientific research and policy agendas. Using a case study method, a questionnaire survey among 99 agro-food companies in Slovakia was carried out to obtain empirical data about the way how they manage, implement and evaluate the innovations. The study outlined the selected aspects and key determinants which affect the motivation of agro-food companies to innovate as well as selected factors influencing the processes of implementation and management of innovation. The research findings also point out that substantial changes will be required in regulation and support of innovations in the agro-food sector in Slovakia. The study could contribute to help the agro-food companies' managers to improve the innovation activities and competitiveness of their companies, and it would be also helpful for public administration in the development of policies and instruments supporting innovations in the agro-food sector.